Minutes of the 23rd Meeting of BRAC University Academic Council (AC) - Academic Council, BRAC University (Vice Chancellor's Office, BRAC University, 2013)
Minutes of the 23rd Meeting of BRAC University Academic Council, held on Sunday, 10th December, 2006.